Problematika Kejurusitaan dalam Menangani Perkara Pada Kantor Pengadilan Agama Kabupaten Bangli - I Wayan Eka Antara; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Warmadewa Press, 2024)
The legal system in Indonesia is based on colonial, ethnic and religious law. This regulation forms the basis for all court decisions, including general courts, state administrative courts, and religious courts. As for the problems: 1) How is the process for implementing jurors based on article 103 of the Republic of Indonesia Law Number 7 of 1989 concerning Religious Courts at the Bangli Regency Religious Court office? 2) What are the inhibiting factors for adversity in handling cases at the Bangli Regency Religious Court office? The purpose of this study is to understand the implementation of jursita based on article 103 of Law No. 7 of 1989 concerning the Religious Courts at the Bangli District Religious Court and to understand the supporting and inhibiting factors of slump at the Bangli Religious Courts, to then find a solution. This study uses empirical methods. Empirical method used by the writer based by the data obtained by the writer from those people whom directly connected with the case matters written on the subject of this study. The bailiff must comply with the direction of the Chief Justice and submit announcements, reprimands, and court decisions in accordance with statutory provisions. If the parties do not provide accurate information, bailiffs may experience difficulties in carrying out their duties. However, they can still be informed about subpoenas by the local village head.